In-Vehicle Information Systems - Štefančić, Gordana; Presečki, Antun; Andrić, Suzana (Promet - Traffic&Transportation, 2002)
The paper considers different systems, including thesystems with autonomous units, which cany all their knowledgewith them, and those with communication units, which informthe driver about the current situation of the road system byradio or other means. The symbols of various messageshave three main goals: to provide instruction, to warn ofoncoming danger, or to give advice regarding parking or lookingfor alternative routes. When not used for these purposes,they are used to provide general information about/he weathe1;temperature or possible attractions. The in-vehicle informationsystems try to assist the motorist in driving, and they arepromoted as part of the comprehensive intelligent transport system.